History of CEFTA 2006 - New challenges and dilemmas - Krum Efremov; Ljupco Velevski; Makedonka Dimitrova (University American College Skopje, 2020)
This paper addresses some historical backgrounds, differences of the structure, opportunities, challenges and dilemmas encountered in the implementation of Agreement on amendment of and accession to the Central European Free Trade Agreement, called CEFTA 2006. In the past 13 years, implementation on the CEFTA 2006 would significantly contribute to the continual efforts for strengthening the regional trade and investment cooperation, further liberalisation of foreign trade exchange, and continuation of activities for harmonisation of trade rules with international and EU standards. Additionally, CEFTA 2006 provides a much more comprehensive framework for development of mutual relations and economic cooperation among the Parties, increasing competitiveness and integration of the Region into the European and global economies. At the same time, in a more of one decade of implementation of CEFTA 2006, Parties still have open dilemmas about the Agreement's proper implementation especially regarding non tariff barriers and consensus as a decision making concept. Climate change as a new threat in world economy is global challenge that will have long term influence into trade policy in the future within developing climate-friendly measures, as a most important priority for prosperity of the planet and humanity.
Keywords: 330; CEFTA 2006; trade; non tariff barriers; regional ownership; climate change.